Formulation and physicochemical evaluation of toothpaste formulated with Thymus vulgaris essential oil - Mohammad Kiani; Farzin Firozian; Shirin Moradkhani (Shahrekord University of Medical Sciences, 2017)
Introduction: Streptococcus mutans is the most common cause of tooth decay. Parabens, and other commonly used as anti-Streptococcus agents in toothpaste industry have numerous side effects such as discoloration of teeth. Thymus vulgaris essential oil has profound antimicrobial activity against a wide range of species. The aim of present study was the aim of the present study was to formulate and evaluate the physicochemical properties of a kind of toothpaste formulated with Thymus vulgaris essential oil. Thyme oil components were also analyzed using gas chromatography-mass spectrometry (GC-MS). Methods: Toothpaste was formulated in forms of gel and opaque and Thyme essence was added to it. The formulation was evaluated in terms of stability in different temperatures, pH, consistency, uniformity, taste, smell, and compatibility with special packaging for toothpaste at three temperatures. Profilometry was used to determine abrasivity. The rate of contaminations with lead and arsenic was determined by atomic absorption. The amount of fluoride was measured by potentiometry. Results: Forty-one different components, representing 99.64% of the total oil were identified in essential oil. Addition of thyme essence to formulation had no deleterious effect in stability, consistency, taste and smell. The pH of opaque and gel formulations was 7.02 and 7.45, respectively. The abrasiveness of opaque and gel formulations was in standard ranges. The fluoride content was 1000 ppm. Lead and arsenic were not detected at all. Conclusion: Formulation of toothpaste with T. vulgaris essential oil was acceptable and might be considered as a desirable herbal toothpaste.